GREB1 role in cellular homeostasis and cancer - Huynh, Vinh Thang (Nanyang Technological University, 2022)
Our understanding of biology is fundamentally rooted in the ever-evolving molecular central dogma, wherein functional protein syntheses begin with transcriptions followed by translations. Decades of work have deepened our knowledge by uncovering labyrinthine and complex layers of regulatory mechanisms, exemplified by the plethora of posttranslational modifications. The work in my Ph.D. has contributed to this ongoing effort as I studied GREB1 regulation of hormonal receptor signaling. The first chapter lays out important background information. First, it provides a general perspective of the mammalian glycosylation realm, emphasizing O-GlcNAcylation in the cytoplasm and the nucleus. After that, estrogen receptor-alpha and GREB1 are introduced, including prior works in Vinay Tergaonkar’s lab, which discover that GREB1 stabilizes ERα and consequentially upregulates ERα signaling and cellular proliferation. In the second chapter, I explain the results from this thesis which characterize GREB1 glycosylation activity in vitro, in yeast, and in breast cancer cells, wherein GREB1 glycosylates ERα T553 and S554 residues. Functionally, O-GlcNAc glycosylations of ERα at T553 and S554 prevent targeting by ubiquitin ligase ZNF598. Furthermore, GREB1 activity depends on the levels of UDP-GlcNAc sugar substrates, and another estrogen-responsive gene, XBP1, is a transcription factor that regulates the hexosamine biosynthetic pathway (HBP), which produces UDP-GlcNAc. Our work presents a compelling case for the ERα-GREB1-XBP1 axis, which creates a positive feedback loop potentiating ERα signaling and cellular proliferation. When looking at Greb1-KO mice, we found a striking resemblance of female reproductive defects between GREB1 loss and ERα loss phenotype. Lastly, this work invites the exploration of GREB1 and GREB1L glycosylation systems, which conserve beyond the animal kingdom.